Coated KSF phosphor, method for producing said phosphor, curable silicone composition containing said phosphor, and optical semiconductor device

JP7634451B2Active Publication Date: 2025-02-21SHIN ETSU CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021147013
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-09
Publication Date
2025-02-21
Estimated Expiration
2041-09-09

AI Technical Summary

Benefits of technology

【0023】 本発明のポリマーによる表面コーティングを有するKSF蛍光体は、高温条件下においてもKSF蛍光体からの酸性物質の放出が抑制され、該蛍光体を含有する硬化性シリコーン組成物の硬化物において、シリコーン樹脂の分解を防止する事ができるため、光半導体素子の封止材用途に有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634451000001
    Figure 0007634451000001
  • Figure 0007634451000002
    Figure 0007634451000002
  • Figure 0007634451000003
    Figure 0007634451000003
Patent Text Reader

Abstract

To provide a KSF phosphor particle suppressed in generation of an acidic substance even under a high temperature condition, and a curable silicone composition containing the phosphor particle.SOLUTION: Coated KSF phosphor particles have a surface coating with a polymer, the polymer is a (meth)acrylic acid ester polymer, a proportion of the polymer is in the range of 0.1 to 20 mass% of the coated KSF phosphor particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to KSF phosphor (manganese-activated silicon complex fluoride phosphor) particles having a polymer surface coating, a curable silicone composition containing the phosphor particles having the polymer surface coating, and an optical semiconductor device encapsulated with a cured product of the curable silicone composition. [Background technology]

[0002] At present, optical semiconductor devices (LEDs) that emit white light by combining blue light-emitting diodes with various phosphors have been put to practical use and are being used in image display devices, lighting devices, and the like.

[0003] In recent years, KSF phosphors have been used as phosphors that emit red fluorescence (Patent Documents 1 and 2), and have attracted attention as materials that can achieve both high luminous efficiency and color rendering. One of the characteristics of KSF phosphors is that they have a narrow half-width in the red emission region, and they have begun to be effectively used in image display devices.

[0004] Meanwhile, curable silicone resins with various phosphors dispersed therein are widely used as LED encapsulants. However, when encapsulants with KSF phosphors dispersed in curable silicone are used for high-output LED applications, there is a problem that the KSF phosphors generate acidic substances in high-temperature environments, which decompose the silicone. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-224536 A [Patent Document 2] International Publication No. 2015 / 093430 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide KSF phosphor particles in which the generation of acidic substances is suppressed even under high-temperature conditions, and a curable silicone composition containing the phosphor particles. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides 1. A coated KSF phosphor particle, comprising: The coated KSF phosphor particles are KSF phosphor particles having a surface coating with a polymer, the polymer being a (meth)acrylic acid ester polymer, and the proportion of the polymer is in the range of 0.1 to 20 mass % of the entire coated KSF phosphor particles.

[0008] The coated KSF phosphor particles of the present invention suppress the release of acidic substances from the KSF phosphor even under high temperature conditions, and in particular, can prevent decomposition of the silicone resin in the cured product of a curable silicone composition containing the phosphor.

[0009] In the coated KSF phosphor particles of the present invention, the KSF phosphor is K2SiF6:Mn 4+ It is preferable that the phosphor is represented by the formula:

[0010] Such KSF phosphors can provide higher luminous efficiency.

[0011] In the coated KSF phosphor particles of the present invention, the (meth)acrylic acid ester polymer preferably contains, as a constituent unit, a (meth)acrylic acid ester having at least one hydrogen atom directly bonded to a silicon atom in one molecule.

[0012] Such polymers have high gas barrier properties, and when coated on the surface of KSF phosphor particles, they can suppress the release of acidic substances from the KSF phosphor in high-temperature environments.

[0013] The present invention also provides a method for producing the coated KSF phosphor particles, comprising the steps of: (1) preparing a coating composition containing (A) a (meth)acrylic acid ester polymer and (B) a solvent capable of dissolving the polymer, and mixing KSF phosphor particles with the coating composition; and (2) A step of volatilizing the solvent The present invention provides a method for producing coated KSF phosphor particles, comprising the steps of:

[0014] Such a method for producing coated KSF phosphor particles makes it possible to efficiently coat the surfaces of the KSF phosphor particles.

[0015] In this case, the KSF phosphor is K2SiF6:Mn 4+ It is preferable to use a phosphor represented by the following formula:

[0016] By using such KSF phosphor particles, coated KSF phosphor particles with higher luminous efficiency can be obtained.

[0017] In the above production method, it is preferable to use, as the (meth)acrylic acid ester polymer, a polymer containing, as a structural unit, a (meth)acrylic acid ester having at least one hydrogen atom directly bonded to a silicon atom in one molecule.

[0018] By using such a polymer, the release of acidic substances from the KSF phosphor can be further suppressed in a high-temperature environment, so that highly stable coated KSF phosphor particles can be obtained.

[0019] The present invention also provides a curable silicone composition comprising the above-mentioned coated KSF phosphor particles.

[0020] The curable silicone composition of the present invention, in its cured form, is capable of preventing decomposition of the silicone by acidic substances derived from the KSF phosphor under high temperature conditions, and is therefore useful as an encapsulant for optical semiconductor elements.

[0021] The present invention also provides an optical semiconductor device comprising an optical semiconductor element encapsulated with a cured product of the above-mentioned curable silicone composition.

[0022] Such optical semiconductor devices have high reliability because the optical semiconductor elements are stably sealed even in high-temperature environments. Effect of the Invention

[0023] The KSF phosphor having a surface coating with the polymer of the present invention is useful as an encapsulant for optical semiconductor elements, because release of acidic substances from the KSF phosphor is suppressed even under high temperature conditions, and decomposition of the silicone resin in the cured product of the curable silicone composition containing the phosphor can be prevented. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] As mentioned above, when an encapsulant with KSF phosphor dispersed in a curable resin is used for high-output LED applications, there is a problem that the KSF phosphor generates acidic substances in high-temperature environments. For this reason, there was a demand for the development of a KSF phosphor that is stable even in high-temperature environments.

[0025] As a result of intensive research into achieving the above-mentioned object, the inventors have found that the above-mentioned problems can be solved by a KSF phosphor having a surface coating made of a specific proportion of a (meth)acrylic acid ester polymer, and have thus completed the present invention.

[0026] That is, the present invention relates to a coated KSF phosphor particle, which is a KSF phosphor particle having a surface coating with a polymer, wherein the polymer is a (meth)acrylic acid ester polymer, and the proportion of the polymer is in the range of 0.1 to 20 mass % of the entire coated KSF phosphor particle.

[0027] The present invention will be described in detail below, but the present invention is not limited thereto.

[0028] [Coated KSF phosphor particles] The coated KSF phosphor particles of the present invention are KSF phosphor particles having a surface coating with a polymer, and are characterized in that the polymer is a (meth)acrylic acid ester polymer.

[0029] The coated KSF phosphor particles may be KSF phosphor particles having a surface coating with the above-mentioned polymer, and the form is not particularly limited. For example, one KSF phosphor particle may be surface-coated with a polymer, or may be an aggregate thereof. Two or more KSF phosphor particles may be surface-coated with a polymer. The surface coating with a polymer may be a single layer or two or more layers, and the two or more surface coatings may be the same or different. An example of two or more KSF phosphor particles surface-coated with a polymer is a particle formed by coating secondary particles of aggregated KSF phosphor particles with a polymer. Each component constituting the coated KSF phosphor particles will be described below.

[0030] [KSF phosphor] KSF phosphor (manganese-activated silicon complex fluoride phosphor) is a red phosphor made by adding Mn to K2SiF6 crystal.

[0031] The KSF phosphor preferably used in the present invention is K2SiF6 with tetravalent Mn added as a luminescent ion (K2SiF6:Mn 4+ ) and emits light at 600 to 660 nm when excited with light with a peak wavelength of 455 nm. 4+ If the phosphor is expressed by the formula (1), a higher luminous efficiency can be obtained.

[0032] The average particle size of the KSF phosphor is preferably 10 to 100 μm, and more preferably 20 to 50 μm. The average particle size in the present invention is the median diameter (D50) in a volume-based particle size distribution obtained by a laser diffraction / scattering method.

[0033] The KSF phosphor may be produced by a conventional method, for example, by dissolving or dispersing metal fluoride raw materials such as silicon fluoride and manganese fluoride in hydrofluoric acid, and then heating and evaporating to dryness.

[0034] [Component (A): (meth)acrylic acid ester polymer] The polymer that coats the surfaces of the KSF phosphor particles of the present invention is a (meth)acrylic acid ester polymer (hereinafter, component (A)). This component has high gas barrier properties, so when coated onto KSF phosphor, it suppresses the release of acidic substances from the KSF phosphor in high-temperature environments.

[0035] In the present invention, (meth)acrylic acid ester refers to an acrylic acid ester, a methacrylic acid ester, or both, and examples of the acrylic acid ester include methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, isopentyl acrylate, n-hexyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isononyl acrylate, n-decyl acrylate, isodecyl acrylate, etc. Examples of the methacrylic acid ester include methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, etc. Among these, preferred are alkyl acrylates and alkyl methacrylates in which the alkyl group has 1 to 12 carbon atoms, particularly preferably 1 to 4 carbon atoms. These may be used alone or in combination of two or more.

[0036] The component (A) preferably contains, as a structural unit, a (meth)acrylic acid ester having at least one hydrogen atom directly bonded to a silicon atom (hereinafter referred to as a SiH group) in one molecule. Such a component (A) may be a polymer or copolymer containing, as a monomer component, a (meth)acrylic acid ester having at least one SiH group in one molecule.

[0037] An example of the (meth)acrylic acid ester having at least one SiH group in one molecule is a compound represented by the following formula (1). [ka] (In the formula, R is a hydrogen atom or a methyl group, and R 1 are independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, R 2 is an alkylene group having 1 to 10 carbon atoms, and n is 0, 1, or 2.

[0038] R 1 Specific examples of the alkyl group include alkyl groups having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, such as a methyl group, an ethyl group, and a propyl group, and aryl groups having 6 to 10 carbon atoms, such as a phenyl group, with a methyl group and a phenyl group being preferred.

[0039] R 2 Examples of the alkylene group include alkylene groups having 1 to 10 carbon atoms, such as a methylene group, an ethylene group, a propylene group, and a butylene group, and an alkylene group having 1 to 3 carbon atoms is preferable.

[0040] The content of (meth)acrylic acid ester units having at least one SiH group per molecule in the component (A) is preferably from 10 to 100 mass %, and more preferably from 20 to 50 mass %.

[0041] The component (A) can be obtained by (co)polymerizing the above (meth)acrylic acid ester using a radical polymerization initiator such as 2,2'-azobisisobutyronitrile (AIBN).

[0042] The molecular weight of the component (A) is preferably 1,000 to 1,000,000, and more preferably 10,000 to 100,000, in terms of polystyrene equivalent number average molecular weight (Mn) measured by gel permeation chromatography (GPC) (developing solvent: tetrahydrofuran).

[0043] The amount of polymer (A) coated on the KSF phosphor is 0.1 to 20% by mass, preferably 1 to 10% by mass, and particularly preferably 1 to 5% by mass, based on the total amount of coated KSF phosphor particles (KSF phosphor particles having a surface coating). If the amount of coating is small, the ability to block acidic substances generated by the KSF phosphor is poor, and if the amount of coating is large, the KSF phosphors may aggregate together, affecting the optical properties of the LED or causing discoloration due to heat.

[0044] [Method of manufacturing coated KSF phosphor particles] The method for producing the KSF phosphor having a surface coating with the polymer of the present invention is not particularly limited, and any known technique may be appropriately adopted.

[0045] The KSF phosphor particles having a surface coating with the polymer of the present invention preferably have (1) preparing a coating composition containing (A) a (meth)acrylic acid ester polymer and (B) a solvent capable of dissolving the polymer (hereinafter referred to as component (B)), and mixing KSF phosphor particles with the coating composition; and (2) A step of volatilizing the solvent The composition is obtained by a production method comprising the steps of:

[0046] Step (2) may be performed after step (1), or steps (1) and (2) may be performed simultaneously, or steps (1) and (2) may be performed repeatedly depending on the desired amount of coating. Coated KSF phosphor particles having different coating layers can also be obtained by repeatedly performing steps (1) and (2) while changing the composition of component (A).

[0047] In step (1), a coating composition containing the component (A) and the solvent (B) can be obtained by using a known stirring, mixing, and dissolving device. The device for mixing the KSF phosphor particles and the coating composition can be set according to the production scale, and examples of the device include a combination of a spatula and a flask or an evaporating dish, a Henschel mixer, a super mixer, and other stirring mixers. In step (2), a known stirring and drying device can be used to volatilize the solvent from the mixture of the KSF phosphor particles and the coating composition. If the stirring and drying device is equipped with a heating means or a decompression means, the solvent can be efficiently volatilized. When steps (1) and (2) are performed simultaneously, a device equipped with a means for sufficiently stirring, mixing, and drying the coating composition containing the KSF phosphor particles, the (A) (meth)acrylic acid ester polymer, and the (B) solvent can be used. In this case, the device can also be equipped with a heating means or a decompression means.

[0048] For example, in the case of a small amount, the KSF phosphor particles can be placed in a container, the coating composition can be added, and the solvent can be evaporated while stirring with a spatula, etc. On the other hand, in the case of polymer coating a large amount of KSF phosphor particles, it is possible to coat them using a stirring device equipped with a degassing device such as an evaporator. Furthermore, if the KSF phosphor particles aggregate during the polymer coating, it is possible to obtain non-aggregated KSF phosphor particles by temporarily removing them from the container, crushing them, and then drying them.

[0049] [Coating composition] The coating composition used in the method for producing coated KSF phosphor particles of the present invention contains KSF phosphor particles, the above-mentioned component (A), and a solvent (component (B)) that dissolves component (A). The coating composition may contain components other than components (A) and (B) as necessary.

[0050] [(B) Component] The solvent for component (B) is not limited as long as it dissolves component (A) and provides a coating composition as a uniform solution, and known organic solvents can be used. For example, aromatic hydrocarbon solvents such as xylene, toluene, and benzene, aliphatic hydrocarbon solvents such as heptane and hexane, halogenated hydrocarbon solvents such as trichloroethylene, perchloroethylene, and methylene chloride, ester solvents such as ethyl acetate, ketone solvents such as methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone, alcohol solvents such as ethanol, isopropanol, and butanol, petroleum solvents such as ligroin, ether solvents such as diethyl ether, rubber volatile oil, and silicone solvents. Among these, aromatic hydrocarbon solvents and ester solvents are preferred. Depending on the desired evaporation rate, one type can be used alone, or two or more types can be combined to form a mixed solvent.

[0051] The blend amount of component (B) may be any amount according to workability, but is preferably 70 to 99.9 mass %, and particularly preferably 80 to 99.5 mass %, of the total coating composition.

[0052] [Other ingredients] Other ingredients include antioxidants.

[0053] [Curable Silicone Composition] The curable silicone composition of the present invention contains a curable silicone resin and the coated KSF phosphor particles. The curable silicone resin is not particularly limited, but examples thereof include those for LED encapsulants such as KER-2936-A / B (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0054] The curable silicone composition of the present invention, in its cured form, is capable of preventing decomposition of the silicone by acidic substances derived from the KSF phosphor under high temperature conditions, and is therefore useful, for example, as an encapsulant for optical semiconductor elements.

[0055] [Optical semiconductor device] The present invention also provides an optical semiconductor device in which an optical semiconductor element is encapsulated with a cured product of the above-described curable silicone composition.

[0056] The coated KSF phosphor particles of the present invention suppress the release of acidic substances from the KSF phosphor even under high temperature conditions, and can prevent decomposition of the silicone resin in the cured product of the curable silicone composition containing the phosphor. Therefore, an optical semiconductor device in which an optical semiconductor element is encapsulated with the cured product of the curable silicone composition is resistant to deterioration over time and highly reliable, since the optical semiconductor element is stably encapsulated even under high temperature conditions. EXAMPLES

[0057] The present invention will be specifically described below using examples, but these examples do not limit the present invention in any way. The non-volatile content of the coating composition was calculated from the mass difference before and after weighing 1.5 g of the composition into a petri dish and heating it under conditions of 105°C for 3 hours. The molecular weight (number average molecular weight Mn, weight average molecular weight Mw) is a value calculated in terms of polystyrene in GPC measurement (developing solvent: tetrahydrofuran). The average particle size is the median diameter (D50) in the volume-based particle size distribution obtained by a laser diffraction / scattering method.

[0058] [Synthesis Example 1] 60 parts by mass of methyl methacrylate, 600 parts by mass of a mixed solvent of isopropyl alcohol (IPA):ethyl acetate = 100:500 (mass ratio), and 0.5 parts by mass of AIBN were stirred at 80 ° C for 3 hours to obtain a coating composition (non-volatile content 8.0 mass %) containing a methyl methacrylate polymer (Mn: 83,540, Mw: 124,550).

[0059] [Synthesis Example 2] 43 parts by mass of methyl methacrylate, 22 parts by mass of a SiH-containing methacrylic acid ester represented by the following formula, 600 parts by mass of a mixed solvent of IPA:ethyl acetate = 100:500 (mass ratio), and 0.5 parts by mass of AIBN were stirred at 80 ° C for 3 hours to obtain a coating composition (non-volatile content 6.0 mass %) containing a SiH group-containing methacrylic acid ester-methyl methacrylate copolymer (Mn: 49,240, Mw: 103,130). 0% by mass was obtained. [ka]

[0060] [Example 1] KSF phosphor (K2SiF6:Mn 4+ 5 g of the methyl methacrylate polymer (D50: 25 μm) was placed in a flask, 1 g of the coating composition containing the methyl methacrylate polymer obtained in Synthesis Example 1 was added, and mixing was performed using a spatula. Mixing was continued for 5 minutes while volatilizing the solvent, to obtain a KSF phosphor having a surface coating with a polymer. The coating amount of the methyl methacrylate polymer relative to the entire KSF phosphor having a polymer coating was 1.6 mass %.

[0061] [Example 2] KSF phosphor (K2SiF6:Mn 4+ 5 g of 1000 g of methacrylic acid ester-methyl methacrylate copolymer (D50: 25 μm) was placed in a flask, and 1 g of the coating composition containing the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer obtained in Synthesis Example 2 was added and mixed using a spatula. Mixing was continued for 5 minutes while volatilizing the solvent, to obtain a KSF phosphor having a polymer surface coating. The coating amount of the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer relative to the entire KSF phosphor having a polymer coating was 1.2 mass %.

[0062] [Example 3] The same procedure as in Example 2 was repeated three times to obtain a KSF phosphor having a polymer surface coating. The coating amount of the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer relative to the entire KSF phosphor having a polymer coating was 3.6 mass %.

[0063] [Comparative Example 1] KSF phosphor (K2SiF6:Mn 4+ 5 g of 1000 g of methacrylic acid ester-methyl methacrylate copolymer (D50: 25 μm) was placed in a flask, and 0.05 g of the coating composition containing the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer obtained in Synthesis Example 2 was added and mixed using a spatula. Mixing was continued for 5 minutes while volatilizing the solvent, to obtain a KSF phosphor having a polymer surface coating. The coating amount of the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer relative to the entire KSF phosphor having a polymer coating was 0.06 mass %.

[0064] [Comparative Example 2] KSF phosphor (K2SiF6:Mn 4+ 5 g of the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer (D50: 25 μm) was placed in a flask, and 20 g of the coating composition containing the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer obtained in Synthesis Example 2 was added and mixed using a spatula. After continuing mixing for 30 minutes while evaporating the solvent, the mixture was thinly spread on a petri dish and naturally dried at 25°C for 12 hours to obtain a KSF phosphor having a polymer surface coating. The coating amount of the SiH group-containing methacrylic acid ester-methyl methacrylate copolymer relative to the entire KSF phosphor having a polymer coating was 26 mass %.

[0065] [Comparative Example 3] KSF phosphor (K2SiF6:Mn 4+5 g of 100% by mass of methacryloxypropyltrimethoxysilane in acetone was added and mixed using a spatula. After mixing for 30 minutes while evaporating the solvent, the mixture was thinly spread on a petri dish and naturally dried at 25°C for 12 hours to obtain a KSF phosphor with a surface coating of a silane coupling agent. The amount of the silane coupling agent coated on the entire KSF phosphor was 2% by mass.

[0066] The KSF phosphors having a surface coating made of a polymer and a silane coupling agent obtained in Examples 1 to 3 and Comparative Examples 1 to 3, and the KSF phosphor having no surface coating (Comparative Example 4) were subjected to the following heat resistance test. The results are shown in Table 1.

[0067] [Heat resistance test] 2g of LED curable silicone resin (KER-2936-A / B, Shin-Etsu Chemical Co., Ltd.) and 0.4g of KSF phosphor were placed in a polyethylene container and mixed, after which 0.8g was weighed out and placed in an aluminum petri dish, and heat resistance was evaluated based on the appearance and mass change after exposure to a 200°C environment for 100 and 300 hours. The appearance was observed visually for color, and the mass change rate was calculated as (mass after a specified time - mass at 0 hours) / mass at 0 hours x 100 (%).

[0068] [Table 1]

[0069] As shown in Table 1, the KSF phosphor particles having a surface coating with a polymer obtained in Examples 1 to 3 had the same appearance and very little weight change even after 300 hours at 200°C, which was a good result, whereas when KSF phosphor particles with a small amount of coating were used as in Comparative Example 1, when a KSF phosphor having a surface coating with a silane coupling agent was used as in Comparative Example 3, and when a KSF phosphor without a surface coating was used as in Comparative Example 4, the mass loss due to decomposition of the silicone resin was very large. Moreover, when KSF phosphor particles with too much coating were used as in Comparative Example 2, discoloration of the methacrylic acid ester polymer itself occurred, making it difficult to apply it to an encapsulant for an optical semiconductor device.

[0070] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.

Claims

1. 1. A coated KSF phosphor particle, comprising: The coated KSF phosphor particles are KSF phosphor particles having a surface coating with a polymer, the polymer being a (meth)acrylic acid ester polymer, and the proportion of the polymer is in the range of 0.1 to 20 mass % of the entire coated KSF phosphor particles; The coated KSF phosphor particles are characterized in that the (meth)acrylic acid ester polymer is a polymer of a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 12 carbon atoms.

2. The KSF phosphor is K 2 SiF 6 : Mn 4+ 2. The coated KSF phosphor particle according to claim 1, wherein the phosphor is represented by the formula:

3. 3. The coated KSF phosphor particle according to claim 1, characterized in that the (meth)acrylic acid ester polymer contains, as a constituent unit, a (meth)acrylic acid ester represented by the following formula (1) having at least one hydrogen atom directly bonded to a silicon atom in one molecule: 【Chemistry 1】 (In the formula, R is a hydrogen atom or a methyl group, R 1 is independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, R 2 is an alkylene group having 1 to 10 carbon atoms, and n is 0, 1, or 2.)

4. A method for producing the coated KSF phosphor particles according to claim 1, comprising the steps of: (1) preparing a coating composition containing (A) a (meth)acrylic acid ester polymer and (B) a solvent capable of dissolving the polymer, and mixing KSF phosphor particles with the coating composition; and (2) A step of volatilizing the solvent A method for producing coated KSF phosphor particles, comprising:

5. The KSF phosphor is 2 SiF 6 : Mn 4+ 5. The method for producing coated KSF phosphor particles according to claim 4, wherein a phosphor represented by the formula:

6. 6. The method for producing coated KSF phosphor particles according to claim 4 or 5, characterized in that the (meth)acrylic acid ester polymer is a polymer containing, as a structural unit, a (meth)acrylic acid ester represented by the following formula (1) having at least one hydrogen atom directly bonded to a silicon atom in one molecule: 【Chemistry 2】 (In the formula, R is a hydrogen atom or a methyl group, R 1 is independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, R 2 is an alkylene group having 1 to 10 carbon atoms, and n is 0, 1, or 2.)

7. A curable silicone composition comprising the coated KSF phosphor particles according to any one of claims 1 to 3.

8. 8. An optical semiconductor device comprising an optical semiconductor element encapsulated with a cured product of the curable silicone composition according to claim 7.

Citation Information

Patent Citations

  • Coated particle and its manufacturing method

    JP2005179502A

  • Method of manufacturing complex fluoride and complex fluoride fluorescent material

    JP2012224536A

  • Display devices containing green-emitting quantum dots and red KSF phosphors

    JP2019502272A

  • Coated manganese-doped phosphor

    JP2019525974A

  • Fluoride phosphor composite, method of manufacturing fluoride phosphor composite, white light emitting apparatus, display apparatus, lighting device, and electronic device

    US20180022993A1